Comparing Web Interaction Models in Developing Regions - Chen, Jay; Dhananjay, Aditya; Amershi, Saleema; Subramanian, Lakshmi (ACM, 2010)
Internet connections in developing regions are scarce and often unreliable. While options for connecting to the Internet are gradually being realized, progress is slow. We observed people performing web search and browsing in a low bandwidth environment in Kerala, India. We found that people in this environment experienced frustration and boredom while waiting for page loads compared to typical experiences in the developed world. Following these observations, we conducted a formal study with 20 participants at the same location comparing the conventional web search and browsing process with an asynchronous queueing model. Participants using the asynchronous queueing system performed as well as the status quo in terms of the number of tasks completed, and we observed greater interaction and information viewed for the asynchronous system. Our participants also preferred the asynchronous system over conventional search. Finally, we found evidence that the asynchronous system would have greater benefits in environments where the network is even more constrained